2018
DOI: 10.1097/prs.0000000000004601
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Three-Dimensional Image Simulation: Patient-Reported Outcomes and Mammometrics in Primary Breast Augmentation

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The use of the BREAST-Q to quantify changes in satisfaction with breasts, psychosocial well-being, and sexual well-being associated with breast augmentation has also been reported in other studies. 3 25 26 27 The comparison of preoperative BREAST-Q scores obtained in the present study with those reported by previous studies 8 18 25 26 showed that, except for the physical well-being domain, the mean domain scores were much lower in this series, suggesting a greater patient dissatisfaction with the measured parameters at baseline. This may be related to differences in perceived body image between Brazilian and international populations, with hypomastia having a greater impact on the quality of life of Brazilian women, or it may be related to overreporting by patients trying to increase their chances to be selected for the surgical procedure provided by the public health system.…”
Section: Discussionsupporting
confidence: 73%
“…The use of the BREAST-Q to quantify changes in satisfaction with breasts, psychosocial well-being, and sexual well-being associated with breast augmentation has also been reported in other studies. 3 25 26 27 The comparison of preoperative BREAST-Q scores obtained in the present study with those reported by previous studies 8 18 25 26 showed that, except for the physical well-being domain, the mean domain scores were much lower in this series, suggesting a greater patient dissatisfaction with the measured parameters at baseline. This may be related to differences in perceived body image between Brazilian and international populations, with hypomastia having a greater impact on the quality of life of Brazilian women, or it may be related to overreporting by patients trying to increase their chances to be selected for the surgical procedure provided by the public health system.…”
Section: Discussionsupporting
confidence: 73%
“…12,13 Preoperative communication and patient education are imperative. 1,2,4,5 Changes communicated in volume measures will be hard for many patients to grasp. Patients communicating their wishes in milliliters may also have unrealistic expectations.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason and because of the lack of other easily communicable parameters, cup size is frequently used in preoperative surgical consultations. [1][2][3][4][5] However, brassiere cup systems and sizes are nonstandardized measures. Different brassiere cup systems, such as the European, French, English, and US systems, are in parallel use in most markets.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns were also raised as to the accuracy of the generated images and what affect this could have on the patient's expected outcomes. [56][57][58][59] Recent advances in this field have focused on converting two-dimensional images captured either with photographs or surface scanners into three-dimensional simulations with much less effort and device requirements. The Crisalix system used in this study is one of these types of systems.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns were also raised as to the accuracy of the generated images and what affect this could have on the patient’s expected outcomes. 56–59…”
Section: Discussionmentioning
confidence: 99%